Influence evaluation simulation of factors on performance indicators of organizational and technological objects based on the seasonality of production - Прокопенко, Тетяна Олександрівна; Куліш, Вікторія Іванівна (Technology audit and production reserves, 2015)
This article discusses the use of statistical methods to investigate the influence of factors on performance indicators of organizational and technological facilities, taking into account the seasonality of production in different industries (chemical, food, etc.). The main aim of this study is to develop a model of influence of factors on performance indicators of organizational and technological facilities, taking into account the seasonality of production, which is based on the methods of correlation and regression analysis. Using these methods allows quantifying the relationship between values in environment where there are a great number of factors, some of which are unknown. This article discussed the presentation of changes in performance within the seasonal organizational and technological facilities due to changes in the accounted factors with an average impact of unaccounted factors. The model allows making alternative scenarios for the strategic management of organizational and technological objects, taking into account the seasonality of production. The model is recommended for use in the development of automated control systems of technological systems of continuous type with the seasonal nature of production, including companies and corporations of the sugar industry. The research results can be applied in decision support systems for the sugar industry.